Ring homomorphisms on real Banach algebras - Takeshi Miura; Sin-Ei Takahasi (International Journal of Mathematics and Mathematical Sciences)
Let B be a strictly real commutative real Banach algebra with the carrier space ΦB. If A is a commutative real Banach algebra, then we give a representation of a ring homomorphism ρ:A→B, which needs not be linear nor continuous. If A is a commutative complex Banach algebra, then ρ(A) is contained in the radical of B.